Evaluating the Nexus between housing and energy sectors: the comparison of urban, Peri-urban and rural housing areas in Zhuhai, China - Cheshmehzangi, Ali (Scientific Research Publishing Inc, 2020)
China has developed several housing policy reforms and has, in recent years, progressed further on developing policies to promote green strategies and energy-saving plans. The urban housing has much benefited from such reforms and plans, while rural housing has experienced minimal change in the past few decades. As a result, this study aims to identify and explore these differences, challenges, and implications that exist between three areas of urban, peri-urban, and rural in a particular case study in China. For this study, selected residential areas in the City of Zhuhai and its peri-urban and rural areas are selected as case studies. A questionnaire survey is conducted to analyze energy and housing conditions across the more prosperous urban, the dynamic and transitory peri-urban, and the less prosperous rural areas. The case studies are analyzed as comparative examples in a hot and humid sub-tropical area of Southern China. The study compares energy and housing conditions and argues potential possibilities and challenges for the future development of housing policy reforms that are the result of current housing development patterns and green strategy situation in China.